Physical Activity, Sleep and Health-related quality of life (HRQOL) for college students in Iraq - Lian, Denise; Atiyah, Halah (Journal of Physical Education, 2024)
This study demonstrates the relationship between physical activity, sleep, and health-related quality of life among college students, reporting gender differences in levels of physical activity and sleep.The sample comprised four hundred twenty male and female students from the University of Baghdad’s College of Physical Education and Sports Sciences. Three questionnaires were finished to gauge the quality of life concerning health, sleep, and physical activity. Stepwise regression, independent t-tests, and descriptive statistics were used to examine the data.The overall sample’s health-related quality of life was strongly predicted by sleep characteristics and vigorous physical activity, according to the results (F = 0.017, p = 0.000). There was no significant correlation found between any level of physical activity and health-related quality of life for females. Still, vigorous and moderate physical activity variables significantly predicted health-related quality of life in males when examined by gender (t = 6.837, df = 309.115, p <.05).Vigorous physical activity and good sleep are beneficial for helping college students improve health-related quality of life, but this benefit may vary by gender.